Identification of Phanerogamae and Cryptogamae in the Campus Environment and Their Utilization as Learning Resources in the Plant Diversity Course - Maya Rahayu; Gigin Ginanjar; Fahmie Firmansyah (Edukasi, 2024)
Identification is the basis for grouping living things. Identification can be done by observing the morphological characteristics of a specimen. This research was conducted to identify the diversity of Phanerogamae and Cryptogamae plant species in the Bina Bangsa University Campus environment and their use as a learning resource for students in plant diversity courses. The research methodology used is an exploratory, descriptive survey method, which collects plant data and observes the morphology of the plants. The research results show two types of plants, namely higher plants (phanerogamae) and lower plants (cryptogamae). Two sub-divisions are found in higher plants, namely the Angiospermae and Gymnospermae sub-divisions. In the Gymnospermae sub-division, 1 class with one order was found, while in the Angiospermae division, two classes were found, namely monocotyledoneae and dicotyledoneae. In the monocotyledoneae, five orders were found with five families, while in the dicotyledoneae class, 12 orders were found with 14 families. In lower plants, the bryophyta and pteridophyta groups were found. The bryophyta division was found to be 1 class with three orders, while the pteridophyta division was two classes with three orders. The diversity of plants in the area also contributes to the development of a green and pleasant environment, while the resources obtained from these plants can support learning processes, particularly in biology education.